The Demand for Mobility: Evidence from an Experiment with Uber Riders - Peter Christensen; Adam Osman (Institute of Labor Economics (IZA), 2021)
Changes in transport costs can affect mobility in ways that differ across the population, affecting the impacts of transport policies. We randomly assign large price reductions on Uber in Egypt over a 3-month period and collect comprehensive data on participant mobility using Google Timeline. A 50% price reduction quadruples Uber usage and induces a 42% increase in total travel. Effects and welfare gains are larger for women, who are less mobile at baseline and perceive public transit as unsafe. The price elasticity of private vehicle kilometers traveled (-1.28) implies that mobility and external costs increase substantially when ride-hailing prices fall.
Keywords: J16; J28; J61; Q55; R48; 330; mobility on demand; ride-hailing; travel safety; travel demand